Preparation method and application of lightweight concrete

By modifying the modified pineapple leaf fiber and polyvinyl alcohol fiber, combined with surfactant, the problem of poor mechanical properties of lightweight concrete is solved, and its compressive strength and crack resistance are improved, which is suitable for construction applications.

CN119161143AActive Publication Date: 2024-12-20HUNAN CSCEC5B CONCRETE +2
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411257305.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-20
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

Due to the large number of pores and poor mechanical properties of existing lightweight concrete, it is difficult to meet the high requirements of modern civil engineering for structural components quality and mechanical properties.

Method used

Modified pineapple leaf fiber and modified polyvinyl alcohol fiber are used to improve the adhesion and stability of the fibers through alkali treatment and benzoylation modification, and polyvinyl acetate is coated on the surface of the polyvinyl alcohol fibers, combining non-ionic and anionic surfactants, forming three-dimensional structures and low interfacial strength, reducing the hydration reaction speed and internal stress.

Benefits of technology

It significantly improves the mechanical properties and durability of lightweight concrete, enhances bubble stability and dispersion, extends service life, and is suitable for the construction field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a preparation method and application of lightweight concrete, and relates to the technical field of concrete. The lightweight concrete is prepared from the following components: cement, fly ash, standard sand, a water reducing agent, a foaming agent, modified pineapple leaf fibers, modified polyvinyl alcohol fibers, a nonionic surfactant, an anionic surfactant and water, the preparation method of the modified pineapple leaf fiber comprises the following steps: carrying out alkali treatment and benzoylation modification on pineapple leaf fiber; the preparation method of the modified polyvinyl alcohol fiber comprises the following step: coating polyvinyl acetate on the surface of the polyvinyl alcohol fiber. The lightweight concrete has good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a preparation method and application of lightweight concrete. Background Art

[0002] Lightweight concrete includes lightweight foam concrete and lightweight aggregate concrete. Lightweight foam concrete is a porous lightweight material composed of a matrix, aggregates, and pores. It has the advantages of light weight, thermal insulation, good earthquake resistance and durability, and high fluidity. It is widely used in building components such as basements, insulation boards, walls, partitions, floor slabs, and roofs. However, lightweight foam concrete has poor mechanical properties due to the presence of a large number of pores. Modern civil engineering constantly puts forward new requirements on the quality and mechanical properties of structural components, which means that higher requirements are placed on the performance of lightweight concrete. It is urgent to provide a lightweight concrete with good mechanical properties. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a lightweight concrete with good mechanical properties and durability.

[0004] The invention also provides a method for preparing the lightweight concrete.

[0005] The present invention also provides application of the lightweight concrete or the concrete prepared by the preparation method.

[0006] A lightweight concrete according to a first aspect of the present invention comprises the following components: Cement, fly ash, standard sand, water reducing agent, foaming agent, modified pineapple leaf fiber, modified polyvinyl alcohol fiber, nonionic surfactant, anionic surfactant and water; Wherein, the preparation method of the modified pineapple leaf fiber comprises the following steps: Pineapple leaf fiber was modified by alkali treatment and benzoylation; The preparation method of the modified polyvinyl alcohol fiber comprises the following steps: The surface of the polyvinyl alcohol fiber is coated with polyvinyl acetate.

[0007] The lightweight concrete according to the embodiment of the present invention has at least the following beneficial effects: The lightweight concrete of the embodiment has good mechanical properties and durability, and has good application prospects in the fields of construction and the like. By alkali treatment of pineapple leaf fiber, hemicellulose, pectin, wax and other substances are removed, the adhesion between pineapple leaf fiber and gel material is improved, and hydroxyl groups can be activated, which helps to promote the reaction between benzoyl chloride and pineapple leaf fiber; and benzoyl modification of pineapple leaf fiber further reduces the hydrophilicity of pineapple leaf fiber, slows down the hydration reaction speed of gel material, and improves the mechanical properties of lightweight concrete. By coating a layer of polyvinyl acetate with weak acidity on the surface of polyvinyl alcohol fiber, the hydration of gel material can be inhibited, the interface strength can be reduced, the amplitude of the increase of internal stress caused by the long service life of lightweight concrete can be reduced, and the service durability of lightweight concrete can be improved.

[0008] Modified pineapple leaf fiber and modified polyvinyl alcohol fiber can reduce the fluidity of cement slurry, resulting in a relatively low drainage rate, and can form a certain three-dimensional structure with each other, adsorb on the surface of gel material and bubbles, thereby improving the stability of bubbles and significantly improving the mechanical properties of lightweight concrete; combined with the coordination between non-ionic surfactants and anionic surfactants, the dispersibility of modified pineapple leaf fiber and modified polyvinyl alcohol fiber can be effectively improved, the surface tension of bubbles can be reduced, the stability of bubbles can be enhanced, thereby enhancing the mechanical properties of lightweight concrete.

[0009] According to some embodiments of the present invention, the lightweight concrete comprises, by weight: 80 to 110 parts of cement, 10 to 17 parts of fly ash, 5 to 15 parts of standard sand, 0.1 to 1 parts of water reducing agent, 0.5 to 1.5 parts of foaming agent, 2 to 4 parts of modified pineapple leaf fiber, 1 to 3 parts of modified polyvinyl alcohol fiber, 1 to 3 parts of non-ionic surfactant, 0.5 to 2 parts of anionic surfactant and 30 to 50 parts of water.

[0010] According to some embodiments of the present invention, the lightweight concrete comprises, by weight: 90 to 100 parts of cement, 12 to 15 parts of fly ash, 8 to 10 parts of standard sand, 0.3 to 0.5 parts of water reducer, 0.7 to 1 parts of foaming agent, 2.5 to 3 parts of modified pineapple leaf fiber, 1.5 to 2 parts of modified polyvinyl alcohol fiber, 1.5 to 2 parts of non-ionic surfactant, 0.9 to 1.5 parts of anionic surfactant and 35 to 45 parts of water.

[0011] According to some embodiments of the invention, the cement comprises Portland cement.

[0012] According to some embodiments of the present invention, the strength grade of the silicate cement is not lower than P.O42.5.

[0013] The term "not less than" means greater than or equal to, and should be understood to include the number.

[0014] According to some embodiments of the present invention, the method for preparing the modified pineapple leaf fiber may include the following steps: Alkali treatment, first water washing, benzoylation modification, second water washing, alcohol washing, and drying.

[0015] According to some embodiments of the present invention, the method for performing the alkali treatment comprises the following steps: The pineapple leaf fibers are soaked in an alkaline aqueous solution.

[0016] According to some embodiments of the present invention, the length of the pineapple leaf fiber is 5 mm to 7 mm. For example, it can be 5 mm, 5.2 mm, 5.4 mm, 5.6 mm, 5.8 mm, 6 mm, 6.2 mm, 6.4 mm, 6.6 mm, 6.8 mm or 7 mm.

[0017] According to some embodiments of the present invention, the diameter of the pineapple leaf fiber is 35 μm to 45 μm, for example, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm, 40 μm, 41 μm, 42 μm, 43 μm, 44 μm or 45 μm.

[0018] According to some embodiments of the present invention, the alkaline aqueous solution contains 12 wt% to 17 wt% of a strong base, for example, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt% or 17 wt%.

[0019] According to some embodiments of the present invention, the mass volume ratio of the pineapple leaf fiber to the alkaline aqueous solution is 1 g: 40 mL to 60 mL. For example, it can be 1 g: 40 mL, 1 g: 45 mL, 1 g: 50 mL, 1 g: 55 mL or 1 g: 60 mL.

[0020] According to some embodiments of the present invention, the strong base comprises an alkali metal hydroxide, and the alkali metal hydroxide comprises at least one of NaOH and KOH.

[0021] According to some embodiments of the present invention, the soaking time is 10 min to 30 min. For example, it can be 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min.

[0022] According to some embodiments of the present invention, the method for performing the benzoylation modification comprises the following steps: In the presence of an alkaline catalyst, the pineapple leaf fiber treated with alkali is reacted with benzoyl chloride to obtain the modified pineapple leaf fiber.

[0023] According to some embodiments of the present invention, the alkaline catalyst includes at least one of pyridine, triethylamine, and sodium carbonate.

[0024] According to some embodiments of the present invention, when the alkaline catalyst is pyridine, the amount of pyridine added is 5 (v / v)% to 15 (v / v)%. For example, it may be 5 (v / v)%, 6 (v / v)%, 7 (v / v)%, 8 (v / v)%, 9 (v / v)%, 10 (v / v)%, 11 (v / v)%, 12 (v / v)%, 13 (v / v)%, 14 (v / v)% or 15 (v / v)%.

[0025] According to some embodiments of the present invention, the mass ratio of the benzoyl chloride to the pineapple leaf fiber is 1:0.4-0.6. For example, it can be 1:0.4, 1:0.42, 1:0.44, 1:0.46, 1:0.48, 1:0.5, 1:0.52, 1:0.54, 1:0.56, 1:0.58 or 1:0.6.

[0026] According to some embodiments of the present invention, the reaction time with the benzoyl chloride is 1 h to 3 h. For example, it can be 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h.

[0027] According to some embodiments of the present invention, the temperature for reacting with the benzoyl chloride is 35° C. to 45° C. For example, it may be 35° C., 36° C., 37° C., 38° C., 39° C., 40° C., 41° C., 42° C., 43° C., 44° C. or 45° C.

[0028] According to some embodiments of the present invention, the solvent used in the benzoylation modification includes acetone, dichloromethane, dichloroethane or dimethylformamide.

[0029] According to some embodiments of the present invention, the alcohol washing comprises washing with anhydrous ethanol.

[0030] According to some embodiments of the present invention, the drying temperature is 60°C to 80°C. For example, it may be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C.

[0031] According to some embodiments of the present invention, the method for preparing the modified polyvinyl alcohol fiber may include the following steps: The polyvinyl alcohol fiber is placed in a polyvinyl acetate emulsion, subjected to ultrasonic treatment, and baked to obtain the modified polyvinyl alcohol fiber.

[0032] According to some embodiments of the present invention, the mass ratio of the polyvinyl alcohol fiber to the polyvinyl acetate in the polyvinyl acetate emulsion is 1:9-12. For example, it can be 1:9, 1:10, 1:11 or 1:12.

[0033] According to some embodiments of the present invention, the method for preparing the modified polyvinyl alcohol fiber further includes solvent water.

[0034] According to some embodiments of the present invention, during the ultrasonic treatment, the mass volume ratio of the polyvinyl alcohol fiber to the solution is 1 g:90 mL to 110 mL. For example, it can be 1 g:90 mL, 1 g:95 mL, 1 g:100 mL, 1 g:105 mL or 1 g:110 mL.

[0035] According to some embodiments of the present invention, the length of the polyvinyl alcohol fiber is 7 mm to 9 mm, for example, 7 mm, 7.5 mm, 8 mm, 8.5 mm or 9 mm.

[0036] According to some embodiments of the present invention, the diameter of the polyvinyl alcohol fiber is 25 μm to 35 μm, for example, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm, 33 μm, 34 μm or 35 μm.

[0037] According to some embodiments of the present invention, the pH of the polyvinyl acetate emulsion is 4 to 5. For example, it can be 4, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9 or 5.

[0038] According to some embodiments of the present invention, the solid content of the polyvinyl acetate emulsion is 10-11 g / 100 mL. For example, it can be 10 g / 100 mL, 10.1 g / 100 mL, 10.2 g / 100 mL, 10.3 g / 100 mL, 10.4 g / 100 mL, 10.5 g / 100 mL, 10.6 g / 100 mL, 10.7 g / 100 mL, 10.8 g / 100 mL, 10.9 g / 100 mL or 11 g / 100 mL.

[0039] According to some embodiments of the present invention, the ultrasonic power of the ultrasonic treatment is 40 kW to 60 kW. For example, it can be 40 kW, 42 kW, 44 kW, 46 kW, 48 kW, 50 kW, 52 kW, 54 kW, 56 kW, 58 kW or 60 kW.

[0040] According to some embodiments of the present invention, the ultrasonic treatment time is 10 min to 20 min. For example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min.

[0041] According to some embodiments of the present invention, the baking temperature is 35°C to 45°C. For example, it may be 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C or 45°C.

[0042] According to some embodiments of the present invention, the baking time is 3 h to 5 h. For example, it can be 3 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h, 4 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h or 5 h.

[0043] According to some embodiments of the present invention, the method for preparing the modified polyvinyl alcohol fiber further includes a third water washing treatment after baking.

[0044] According to some embodiments of the present invention, the water reducer includes a polycarboxylate water reducer.

[0045] According to some embodiments of the present invention, the nonionic surfactant includes a polyoxyethylene nonionic surfactant.

[0046] According to some embodiments of the present invention, the polyoxyethylene nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether.

[0047] According to some embodiments of the present invention, the anionic surfactant includes a sulfonate type anionic surfactant.

[0048] According to some embodiments of the present invention, the sulfonate type anionic surfactant includes at least one of sodium dodecylbenzene sulfonate, sodium diisooctyl sulfosuccinate, sodium dibutylnaphthalene sulfonate, and sodium heavy alkylbenzene sulfonate.

[0049] According to some embodiments of the present invention, the foaming agent includes a HTW-I type composite foaming agent.

[0050] The method for preparing the above-mentioned lightweight concrete according to the second aspect of the embodiment of the present invention comprises the following steps: S1, mixing a water reducing agent with water to obtain a mixture A; S2, adding cement, fly ash and standard sand to the mixture A, and mixing to obtain a mixture B; S3, adding a blowing agent to the mixture B, and mixing to obtain a mixture C; S4, adding modified pineapple leaf fiber, modified polyvinyl alcohol fiber, nonionic surfactant and anionic surfactant into the mixture C to obtain cement slurry; pouring, demoulding and curing are carried out successively to obtain lightweight concrete.

[0051] The application of the above-mentioned lightweight concrete or the lightweight concrete prepared by the above-mentioned preparation method in the field of construction according to the third aspect of the present invention.

[0052] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION

[0053] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0054] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0055] In the description of the present invention, if there is a description of first, second, third, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the sequence of the indicated technical features.

[0056] In the description of the present invention, the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.

[0057] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0058] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0059] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0060] "Mass parts" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.

[0061] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±5%.

[0062] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0063] In the examples of the present application, unless otherwise specified, P·O42.5 ordinary Portland cement was purchased from Hunan Yiyang Conch Cement Co., Ltd.; Fly ash, first-grade fly ash, was purchased from Jining Hengzhi New Building Materials Co., Ltd.; Standard sand was purchased from Xiamen Ace Standard Sand Co., Ltd. The polycarboxylate water reducer was Point-TS1 polycarboxylate water reducer purchased from Fujian Kezhijie New Materials Co., Ltd. The foaming agent was HTW-I type composite foaming agent purchased from Henan Huatai Building Materials Development Co., Ltd.; Polyvinyl acetate emulsion, brand 8482, purchased from Celanese Corporation, solid content 53%.

[0064] The preparation method of modified pineapple leaf fiber is as follows: 10 g of pineapple leaf fiber (about 6 mm in length and about 40 μm in average diameter) was soaked in 50 mL of 15wt% NaOH aqueous solution for 20 min. After washing the fiber with clean water, it was placed in 60 mL of acetone solution containing 5 g of benzoyl chloride and 6 mL of pyridine at 40 °C for reaction for 2 h. The fiber was washed with clean water and then soaked in anhydrous ethanol for 1 h to remove unreacted benzoyl chloride. The fiber was washed with clean water and dried at 70 °C to obtain modified pineapple leaf fiber.

[0065] The preparation method of modified polyvinyl alcohol fiber is as follows: 20 g of polyvinyl acetate emulsion was diluted to 100 mL with deionized water, 1 g of polyvinyl alcohol fiber (about 8 mm in length and about 31 μm in average diameter) was immersed in the diluted polyvinyl acetate emulsion, stirred, and treated with ultrasound (50 kW) for 15 min. The polyvinyl alcohol fiber was taken out, baked at 40 °C for 4 h, and then washed with clean water to obtain modified polyvinyl alcohol fiber.

[0066] Example 1 This example provides a lightweight concrete, the raw material composition is as follows by weight: P·O42.5 ordinary Portland cement 100 parts; 15 parts of fly ash; 10 parts of standard sand; 0.5 parts of polycarboxylate water reducer; 1 part of foaming agent; 3 parts of modified pineapple leaf fiber; 2 parts of modified polyvinyl alcohol fiber; 2 parts of fatty alcohol polyoxyethylene ether; 1.5 parts of sodium dodecylbenzene sulfonate; 45 parts of water.

[0067] This example also provides a method for preparing the lightweight concrete, the steps are as follows: S1, mixing the polycarboxylate water reducer with water to obtain a mixture A; S2, adding P·O42.5 ordinary Portland cement, fly ash and standard sand to mixture A, and continuing to stir evenly to obtain mixture B; S3, adding a foaming agent to mixture B, and continuing stirring for 2 min to obtain mixture C; S4, adding modified pineapple leaf fiber, modified polyvinyl alcohol fiber, fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate to mixture C, stirring well to obtain cement slurry; pouring, demoulding and curing are carried out in sequence to obtain lightweight concrete.

[0068] Example 2 This example provides a lightweight concrete, the raw material composition is as follows by weight: P·O42.5 Ordinary Portland Cement 90 parts; 12 parts of fly ash; 8 parts of standard sand; 0.3 parts of polycarboxylate water reducer; 0.7 part of foaming agent; 2.5 parts of modified pineapple leaf fiber; 1.5 parts of modified polyvinyl alcohol fiber; 1.5 parts of alkylphenol polyoxyethylene ether; 0.9 parts of sodium dibutylnaphthalenesulfonate; 35 parts water.

[0069] This example also provides a method for preparing the lightweight concrete, the steps are as follows: S1, mixing the polycarboxylate water reducer with water to obtain a mixture A; S2, adding P·O42.5 ordinary Portland cement, fly ash and standard sand to mixture A, and continuing to stir evenly to obtain mixture B; S3, adding a foaming agent to mixture B, and continuing stirring for 2 min to obtain mixture C; S4, adding modified pineapple leaf fiber, modified polyvinyl alcohol fiber, alkylphenol polyoxyethylene ether and sodium dibutylnaphthalene sulfonate to mixture C, stirring well to obtain cement slurry; pouring, demoulding and curing are carried out in sequence to obtain lightweight concrete.

[0070] Comparative Example 1 This example provides a lightweight concrete, the raw material composition is as follows by weight: P·O42.5 ordinary Portland cement 100 parts; 15 parts of fly ash; 10 parts of standard sand; 0.5 parts of polycarboxylate water reducer; 1 part of foaming agent; 3 parts of alkali-treated pineapple leaf fiber; 2 parts of modified polyvinyl alcohol fiber; 2 parts of fatty alcohol polyoxyethylene ether; 1.5 parts of sodium dodecylbenzene sulfonate; 45 parts of water.

[0071] Wherein, the preparation method of alkali-treated pineapple leaf fiber is as follows: The pineapple leaf fibers (about 6 mm in length and about 40 μm in average diameter) were soaked in a 20% NaOH aqueous solution for 20 min, washed with clean water, and dried at 70°C to obtain alkali-treated pineapple leaf fibers.

[0072] This example also provides a method for preparing the lightweight concrete, the steps are as follows: S1, mixing the polycarboxylate water reducer with water to obtain a mixture A; S2, adding P·O42.5 ordinary Portland cement, fly ash and standard sand to mixture A, and continuing to stir evenly to obtain mixture B; S3, adding a foaming agent to mixture B, and continuing stirring for 2 min to obtain mixture C; S4, adding modified pineapple leaf fiber, modified polyvinyl alcohol fiber, fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate to mixture C, stirring well to obtain cement slurry; pouring, demoulding and curing are carried out in sequence to obtain lightweight concrete.

[0073] Comparative Example 2 This example provides a lightweight concrete, the raw material composition is as follows by weight: P·O42.5 ordinary Portland cement 100 parts; 15 parts of fly ash; 10 parts of standard sand; 0.5 parts of polycarboxylate water reducer; 1 part of foaming agent; 3 parts of modified pineapple leaf fiber; 2 parts of polyvinyl alcohol fiber; 2 parts of fatty alcohol polyoxyethylene ether; 1.5 parts of sodium dodecylbenzene sulfonate; 45 parts of water.

[0074] This example also provides a method for preparing the lightweight concrete, the steps are as follows: S1, mixing the polycarboxylate water reducer with water to obtain a mixture A; S2, adding P·O42.5 ordinary Portland cement, fly ash and standard sand to mixture A, and continuing to stir evenly to obtain mixture B; S3, adding a foaming agent to mixture B, and continuing stirring for 2 min to obtain mixture C; S4, adding modified pineapple leaf fiber, polyvinyl alcohol fiber, fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate to mixture C, stirring well to obtain cement slurry; pouring, demoulding and curing are carried out in sequence to obtain lightweight concrete.

[0075] Comparative Example 3 This example provides a lightweight concrete, the raw material composition is as follows by weight: P·O42.5 ordinary Portland cement 100 parts; 15 parts of fly ash; 10 parts of standard sand; 0.5 parts of polycarboxylate water reducer; 1 part of foaming agent; 3 parts of modified pineapple leaf fiber; 2 parts of modified polyvinyl alcohol fiber; 1.5 parts of sodium dodecylbenzene sulfonate; 45 parts of water.

[0076] This example also provides a method for preparing the lightweight concrete, the steps are as follows: S1, mixing the polycarboxylate water reducer with water to obtain a mixture A; S2, adding P·O42.5 ordinary Portland cement, fly ash and standard sand to mixture A, and continuing to stir evenly to obtain mixture B; S3, adding a foaming agent to mixture B, and continuing stirring for 2 min to obtain mixture C; S4, adding modified pineapple leaf fiber, modified polyvinyl alcohol fiber and sodium dodecylbenzene sulfonate to mixture C, stirring well to obtain cement slurry; pouring, demoulding and curing are carried out in sequence to obtain lightweight concrete.

[0077] Test example 1. According to the test method in JG / T 266-2011 "Foamed Concrete", the compressive strength of the lightweight concrete (size 100 mm×100 mm×100 mm) of Examples 1-2 and Comparative Examples 1-3 cured in a standard curing room for 7 days and 28 days was tested respectively.

[0078] The test results are shown in Table 1.

[0079] Table 1

[0080] 2. The crack resistance of the lightweight concrete of Examples 1-2 and Comparative Examples 1-2 was tested with reference to JC / T 951-2005 "Test Method for Cement Mortar Cracking Resistance". The specific method is as follows: The test was carried out in a laboratory at 20±1℃ and relative humidity (43±2)%. The cement slurry was poured into the template and smoothed. The fan (located 150 mm from the short side of the mold, the center of the fan blade was parallel to the specimen surface, and the average wind speed was 5 m / s) was immediately turned on to blow toward the specimen surface, and the iodine tungsten lamp (1000W, located 1.2 m above the horizontal center line of the specimen and 150 mm from the long side of the mold) was turned on; the fan was turned off after 3 days, and the iodine tungsten lamp was turned off after 4 hours. The specimen was cured in the laboratory for 360 days, and the initial cracking time (cracking age) was recorded.

[0081] The test results are shown in Table 2.

[0082] Table 2

[0083] In summary, the lightweight concrete of Examples 1-2 has good compressive strength and crack resistance.

[0084] Compared with Example 1, the modified pineapple leaf fiber in the lightweight concrete of Comparative Example 1 has weakened compressive and crack resistance after being modified by benzoylation. This may be because the benzoylation modification can reduce the water absorption of plant fibers, slow down the hydration reaction rate of gel materials, improve the interaction between pineapple leaf fibers and gel materials, reduce concentrated stress, and thus improve compressive and crack resistance.

[0085] Compared with Example 1, the lightweight concrete of Comparative Example 2 replaces the modified polyvinyl alcohol fiber with polyvinyl alcohol fiber, and the compressive and crack resistance performance is weakened. This may be due to the lack of polyvinyl acetate-coated polyvinyl alcohol fiber, and the hydration reaction rate of the gel material cannot be effectively suppressed, resulting in weakened compressive and crack resistance.

[0086] Compared with Example 1, the lightweight concrete of Comparative Example 3 lacks fatty alcohol polyoxyethylene ether and its compressive strength becomes poor.

[0087] The embodiments of the present invention are described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A lightweight concrete, characterized in that: Includes the following components: Cement, fly ash, standard sand, water reducing agent, foaming agent, modified pineapple leaf fiber, modified polyvinyl alcohol fiber, nonionic surfactant, anionic surfactant and water; Wherein, the preparation method of the modified pineapple leaf fiber comprises the following steps: Pineapple leaf fiber was modified by alkali treatment and benzoylation; The preparation method of the modified polyvinyl alcohol fiber comprises the following steps: The surface of the polyvinyl alcohol fiber is coated with polyvinyl acetate.

2. The lightweight concrete according to claim 1, characterized in that: The lightweight concrete comprises, by weight: 80 to 110 parts of cement, 10 to 17 parts of fly ash, 5 to 15 parts of standard sand, 0.1 to 1 part of water reducing agent, 0.5 to 1.5 parts of foaming agent, 2 to 4 parts of modified pineapple leaf fiber, 1 to 3 parts of modified polyvinyl alcohol fiber, 1 to 3 parts of nonionic surfactant, 0.5 to 2 parts of anionic surfactant and 30 to 50 parts of water; Preferably, the lightweight concrete comprises, by weight: 90 to 100 parts of cement, 12 to 15 parts of fly ash, 8 to 10 parts of standard sand, 0.3 to 0.5 parts of water reducer, 0.7 to 1 parts of foaming agent, 2.5 to 3 parts of modified pineapple leaf fiber, 1.5 to 2 parts of modified polyvinyl alcohol fiber, 1.5 to 2 parts of non-ionic surfactant, 0.9 to 1.5 parts of anionic surfactant and 35 to 45 parts of water.

3. The lightweight concrete according to claim 1, characterized in that: The method for carrying out the alkali treatment comprises the following steps: Soaking pineapple leaf fibers in an alkaline aqueous solution; And / or, the method for performing the benzoylation modification comprises the following steps: In the presence of an alkaline catalyst, the pineapple leaf fiber treated with alkali is reacted with benzoyl chloride to obtain the modified pineapple leaf fiber.

4. The lightweight concrete according to claim 3, characterized in that: The alkaline aqueous solution contains 12 wt% to 17 wt% of a strong base; And / or, the strong base includes at least one of NaOH and KOH; And / or, the soaking time is 10 min to 30 min.

5. The lightweight concrete according to claim 3, characterized in that: The alkaline catalyst includes at least one of pyridine and triethylamine; And / or, the mass ratio of the benzoyl chloride to the pineapple leaf fiber is 1:0.4-0.6; and / or, the reaction time with the benzoyl chloride is 1 h to 3 h; And / or, the temperature for reacting with the benzoyl chloride is 35° C. to 45° C.

6. The lightweight concrete according to claim 1, characterized in that: The preparation method of the modified polyvinyl alcohol fiber comprises the following steps: The polyvinyl alcohol fiber is placed in a polyvinyl acetate emulsion, subjected to ultrasonic treatment, and baked to obtain the modified polyvinyl alcohol fiber; Preferably, the solid content of the polyvinyl acetate emulsion is 10-11 g / 100 mL; Preferably, the pH of the polyvinyl acetate emulsion is 4 to 5; Preferably, the mass ratio of the polyvinyl alcohol fiber to the polyvinyl acetate in the polyvinyl acetate emulsion is 1:9-12.

7. The lightweight concrete according to claim 1, characterized in that: The nonionic surfactant includes a polyoxyethylene type nonionic surfactant; And / or, the anionic surfactant includes a sulfonate type anionic surfactant.

8. The lightweight concrete according to claim 7, characterized in that: The polyoxyethylene type nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether; And / or, the sulfonate type anionic surfactant includes at least one of sodium dodecylbenzene sulfonate, sodium diisooctyl sulfosuccinate, sodium dibutylnaphthalene sulfonate, and sodium heavy alkylbenzene sulfonate.

9. The method for preparing lightweight concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, mixing a water reducing agent with water to obtain a mixture A; S2, adding cement, fly ash and standard sand to the mixture A, and mixing to obtain a mixture B; S3, adding a blowing agent to the mixture B, and mixing to obtain a mixture C; S4, adding modified pineapple leaf fiber, modified polyvinyl alcohol fiber, nonionic surfactant and anionic surfactant into the mixture C to obtain cement slurry; pouring, demoulding and curing are carried out successively to obtain lightweight concrete.

10. Use of the lightweight concrete according to any one of claims 1 to 8 or the lightweight concrete prepared by the preparation method according to claim 9 in the field of construction.

Citation Information

Patent Citations

  • Composite fiber reinforced foam concrete and preparation method thereof

    CN102199044A

  • High-volume coal ash ceramsite foam concrete and preparation method thereof

    CN104446603A

  • Bamboo fiber coated with polyvinyl acetate and preparation method of bamboo fiber

    CN105239399A

  • Foam concrete

    CN110183185A

  • Basalt fiber for alkali-resistant cement concrete and preparation method thereof

    CN111777348A